MANAGERS PERCEPTIONS AND MITIGATION STRATEGIES AMIDST COVID-19 PANDEMIC - THE CASE OF A NATURE-BASED TOURISM DESTINATION IN GUNUNG CIREMAI NATIONAL PARK, INDONESIA - Nugroho, Prasetyo; Mursyid, Mufaiz Fasyah (Media Konservasi, 2022)
ABSTRACT COVID-19 pandemic has deteriorated nature-based tourism sectors around the world. Indeed, tourism site managers’ perceptions of and mitigation strategies to COVID-19 play a significant role in ensuring tourism operationalization and its management amidst pandemics. Using the case of Curug Cipeteuy, a community-based tourism destination in Gunung Ciremai National Park (GCNP), we investigate managers perceptions on COVID-19 and understand their mitigation strategies amidst the COVID-19 pandemic. A questionnaire survey, depth interviews, and field observation were conducted. We found that while managers' opinion of COVID-19 was relatively low, they hold high agreement in supporting tourism development amidst the COVID-19 pandemic. These could be related to those managers who are proud of tourism and its promising benefits to their area. Furthermore, both structural and non-structural mitigation strategies were done to overcoming pandemic impacts and inviting visitors. Key words: Curug Cipeteuy, mitigation, COVID-19, community-based tourism, national park